AGE MORPHOLOGY OF THE ADRENAL GLANDS IN CHICKENS (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
The histological structure of the adrenal glands of birds was studied and the localization of interrenalocytes of the internal zones of types I, II, III and the subcapsular gland, the shape of cell nuclei and nucleoli, and the morphological features of the structure of adrenalinocytes and noradrenalinocytes were determined.